Improving Nursing Night Shifts: The Importance of Low Light and Proper Breaks (Global Journal of Management and Business Research, 2025)
The article explores the physiological importance of circadian rhythms regulated by hormones like melatonin and cortisol and reviews studies demonstrating the benefits of dim lighting and structured naps during shifts Evidence from international research such as a Brazilian study on nap duration highlights the optimal 2 1 3-hour nap window for recovery and performance However Ontario hospitals often rely on informal tacit agreements for breaks lacking formal policies or proper facilities to support restorative rest The article calls for action by Accreditation Canada and hospital councils to adopt evidence-based policies Recommendations include dimming night time lighting to protect circadian rhythms and formalizing extended supported break periods
Keywords: nurses; working conditions; night shifts; circadian rhythm; melatonin; cortisol; ambient lighting; rest breaks; sleep deprivation